2010
DOI: 10.3998/ark.5550190.0010.e27
|View full text |Cite
|
Sign up to set email alerts
|

[3+2] Cycloaddition reaction between aliphatic alkynes and oxaziridines

Abstract: Alkyl, aryl and acyl-substituted pyrrolidinones as an alternative to isoxazolines can be formed by [3+2] cycloaddition reactions between alkyl oxaziridines and aliphatic alkynes. The structures of isolated products change with oxaziridines Ar groups and with alkynes R and R' groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This and the preceding results are best rationalized by a synchronous [3+2] cycloaddition as recently reported for reaction with alkenes and alkynes [17][18][19] rather than by a 1,3dipolar mechanism, such as for the reactions with nitrones. [10][11][12][13][14][15][16] In summary, we have applied a [3+2] cycloaddition between oxaziridines and nitriles for the synthesis of the 2,3dihydro-1,2,4-oxadiazoles.…”
Section: Scheme 2 [3+2]-cycloaddition Reaction Between Oxaziridines and Alkynessupporting
confidence: 79%
See 1 more Smart Citation
“…This and the preceding results are best rationalized by a synchronous [3+2] cycloaddition as recently reported for reaction with alkenes and alkynes [17][18][19] rather than by a 1,3dipolar mechanism, such as for the reactions with nitrones. [10][11][12][13][14][15][16] In summary, we have applied a [3+2] cycloaddition between oxaziridines and nitriles for the synthesis of the 2,3dihydro-1,2,4-oxadiazoles.…”
Section: Scheme 2 [3+2]-cycloaddition Reaction Between Oxaziridines and Alkynessupporting
confidence: 79%
“…Recently, a [3+2]-cycloaddition reaction between oxaziridines and unactivated terminal alkynes was reported. 17,18 The novelty of this reaction lies in the oxaziridine C-O bond disconnection and the synchronous attack on the triple bond. In detail, the oxygen atom at the internal position and the carbon atom at the terminal position interact.…”
Section: Scheme 1 Synthesis Of 23-dihydro-124-oxadiazoles By Cycloadditionmentioning
confidence: 99%
“…Troisi and co-workers demonstrated that electron-rich alkenes react with oxaziridine 2 to give 3,5-diarylisoxazoline 198 with moderate to excellent cis selectivity (eq 37 ). 134 Aryl 135 and aliphatic 136 terminal alkynes are also competent reaction partners; however, product distributions are highly variable, depending on the substrate. Internal alkynes and benzonitriles 137 have also been utilized to yield 5-acylisoxazolines and 2,3-dihydro-1,2,4-oxadizole products, respectively.…”
Section: Reactivity Of Oxaziridinesmentioning
confidence: 99%
“…It was considerd that the strained oxaziridine ring of these heterobicyclic compounds would be more reactive either than the oxazoline N-oxides 4-13 or than the simple uncondensed oxaziridines. [14][15][16][17] Thus, oxaziridine 6 4a was react-…”
Section: Figure 1 Cycloadducts By Oxazoline N-oxidementioning
confidence: 99%